Identifying Patients Who May Be Candidates for a Clinical Trial of Salvage Accelerated Partial Breast Irradiation after Previous Whole Breast Irradiation. (3rd December 2012) - Li, Linna; Li, Tianyu; Cohen, Randi J.; Anderson, Penny R.; Goldstein, Lori J.; Bleicher, Richard J.; Freedman, Gary M.
Abstract : Background and Objectives . Accelerated partial breast irradiation (APBI) has been proposed as an alternative to salvage mastectomy for patients with ipsilateral breast tumor recurrence (IBTR) after prior breast conservation. We studied factors that are associated with a more favorable local recurrence profile that could make certain patients eligible for APBI. Methods . Between 1980 and 2005, 157 Stage 0–II breast cancer patients had an IBTR treated by mastectomy. Clinical and pathological features were analyzed to identify factors associated with favorable IBTR defined as unifocal DCIS or T1 ≤ 2 cm, without skin involvement, and >2 year interval from initial treatment. Results . Median followup was 140 months and time to recurrence was 73 months. Clinical stage distribution at recurrence was DCIS in 32 pts (20%), T1 in 90 pts (57%), T2 in 14 pts (9%), T3 in 4 pts (3%), and T4 in 9 pts (6%). IBTR was classified as favorable in 71%. Clinical stage of IBTR predicted for pathologic stage –95% of patients with clinical T1 IBTR had pathologic T1 disease at salvage mastectomy ( P < 0.0001 ) . Conclusions . Clinical stage at presentation strongly correlated with pathologic stage at mastectomy. More than 70% of recurrences were favorable and may be appropriate candidates for salvage APBI trials.